Ideal Dalam Semigrup Ternari Komutatif - Noverly Cloren Pattinasarany (Tensor: Pure and Applied Mathematics Journal, 2020)
Algebra is a branch of mathematics that deals with mathematical objects (say, numbers with no known exact value), and uses symbols such as x and y to study them. In algebra, the properties possessed by the operations that can be performed on the object (think addition and multiplication) are studied, and then become "weapons" when we are faced with a problem related to that object. In the structure of algebra, there are many theories such as groups, abelian groups, and semigroups. In semigroups only use binary operations, this makes researchers want to make research on semigroups using ternary surgery, the ideal structure in semigroup commutative ternary. So that we can find out the ideal structure in semigroup commutative fingers.